Assessment of subchondral bone marrow lesions in knee osteoarthritis by MRI: a comparison of fluid sensitive and contrast enhanced sequences. Issue 1 (December 2016) - Nielsen, Flemming; Egund, Niels; Jørgensen, Anette; Peters, David; Jurik, Anne
Abstract Background Bone marrow lesions (BMLs) in knee osteoarthritis (OA) can be assessed using fluid sensitive and contrast enhanced sequences. The association between BMLs and symptoms has been investigated in several studies but only using fluid sensitive sequences. Our aims were to assess BMLs by contrast enhanced MRI sequences in comparison with a fluid sensitive STIR sequence using two different segmentation methods and to analyze the association between the MR findings and disability and pain. Methods Twenty-two patients (mean age 61 years, range 41–79 years) with medial femoro-tibial knee OA obtained MRI and filled out a WOMAC questionnaire at baseline and follow-up (median interval of 334 days). STIR, dynamic contrast enhanced-MRI (DCE-MRI) and fat saturated T1 post-contrast (T1 CE FS) MRI sequences were obtained. All STIR and T1 CE FS sequences were assessed independently by two readers for STIR-BMLs and contrast enhancing areas of BMLs (CEA-BMLs) using manual segmentation and computer assisted segmentation, and the measurements were compared. DCE-MRIs were assessed for the relative distribution of voxels with an inflammatory enhancement pattern, Nvoxel, in the bone marrow. All findings were compared to WOMAC scores, including pain and overall symptoms, and changes from baseline to follow-up were analyzed. Results The average volume of CEA-BML was smaller than the STIR-BML volume by manual segmentation. The opposite was found for computer assisted segmentation where the average CEA-BML volume was larger than the STIR-BML volume. The contradictory finding by computer assisted segmentation was partly caused by a number of outliers with an apparent generally increased signal intensity in the anterior parts of the femoral condyle and tibial plateau causing an overestimation of the CEA-BML volume. Both CEA-BML, STIR-BML and Nvoxel were significantly correlated with symptoms and to a similar degree. A significant reduction in total WOMAC score was seen at follow-up, but no significant changes were observed for either CEA-BML, STIR-BML or Nvoxel . Conclusions Neither the degree nor the volume of contrast enhancement in BMLs seems to add any clinical information compared to BMLs visualized by fluid sensitive sequences. Manual segmentation may be needed to obtain valid CEA-BML measurements.